Parametric Analog Signal Amplification Applied to Nanoscale CMOS Technologies - Oliveira, João P.; Goes, João (Springer New York : Imprint: Springer, 2012)
This book is dedicated to the analysis of parametric amplification with special emphasis on the MOS discrete-time implementation. This implementation is demonstrated by the presentation of several circuits where the MOS parametric amplifier cell is used: small gain amplifier, comparator with embedded pre-amplification, discrete-time mixer/IIR-Filter, and analog-to-digital converter (ADC).  Experimental results are shown to validate the overall design technique. Provides the complete theoretical analysis, supported by electrical simulations, of the parametric amplification technique in both continuous time and discrete time domains; Describes the design flow of an ADC fully based on discrete-time parametric amplification in CMOS technology; Presents a high speed time-interleaved pipeline ADC, based on parametric MOS amplification techniques described, complementing theory discussed with experimental results.